(3CSGSjGJ Yde GdGbJUGO (B/s - (3GdfLaj, SGde Jhajbs ((3GdbGgQI(B: s (3GdOGQ GdOhdjI ddGSJKeGQGJ GdKbGajI(B, s, 2000)
(3eHGOF GbJUGOjI QFjSjI Mhd GdGbJUGO GdLRFj h JfGhd GdWdH h GdYQV h GdJhGRf h cPG GdGfJGL h GdJcGdja GdGfJGLjI ceG Je GdJWQb Gdi eaGgje EbJUGOjI QFjSI Mhd GdGbJUGO Gdcdj h GdJWQb Gdi GdfXQjI GdcdGSjcjI aj GdONd h GdGSJNOGe h GdfXQjI GdcfRjI eY JfGhd GdGbJUGO Gdcdj h GdeJZjQGJ GdQFjSjI (B( (3GdJfXje GdJLGQI GdNGQLjI GdJfejI h Gdfeh GdGbJUGOj(B)s
Keywords: (3GdGbJUGOs; (3GdGbJUGO Gdcdjs; (3GdGbUGO GdLRFjs